PENGARUH PENERAPAN STRATEGI EXAMPLE NON EXAMPLE BERBASIS MEDIA KONKRET TERHADAP HASIL BELAJAR IPA - Nurjannah Nurjannah; Safei Safei; Rosdiana Rosdiana; Fajri Basam (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study where: 1) To describe the science learning outcomes before applying theconcrete media-based example non example strategy to the fourth grade at SDN 017 BonraKab.Polman. 2) To describe the learning outcomes after applying the concrete media-based examplenon-example strategy to the fourth grade at SDN 017 Bonra Kab.Polman. 3) To find out the effectof the application of the example non example strategy based on concrete media affect the sciencelearning outcomes of SDN 017 Bonra Kab. Polman. This study uses a quantitative approach with apre-experimental design and a one-group pretest-posttest research design. The population in thisstudy were all students of four grade class SDN 017 Bonra, totaling 18 people. The samplingtechnique used was the saturated sample technique. The instruments used in this research were testsand documentation. Data analysis techniques used were descriptive statistics and inferentialstatistics. Based on the results of research using descriptive statistics, the average value before theimplementation of the concrete media-based example non example strategy was 31.39 and theaverage value after the concrete media-based example non-example strategy was 81.39. The results ofinferential statistical analysis obtained the value of tcount = 23,805 and the value of ttable = 1,739,then tcount> ttable, which is 23,805> 1,739. It can be said that there was an effect of implementingan example non example strategy based on concrete media on student learning outcomes in sciencesubjects in class IV SDN 017 Bonra Kab.Polman. The implications of this study were (1) Forteachers, the application of a concrete media-based example non-example strategy can improvestudent learning outcomes. (2) For schools, it can improve the quality of teaching andlearning well by using learning strategies